2011
DOI: 10.1123/jpah.8.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Active Commuting to School and Association With Physical Activity and Adiposity Among US Youth

Abstract: Background Walking or bicycling to school (ie, active commuting) has shown promise for improving physical activity and preventing obesity in youth. Our objectives were to examine, among US youth, whether active commuting was inversely associated with adiposity and positively associated with moderate-to-vigorous physical activity (MVPA). We also examined whether MVPA mediated the relationships between active commuting and adiposity. Methods Using data of participants aged 12 to 19 years from the US National H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
120
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 34 publications
(37 reference statements)
15
120
2
7
Order By: Relevance
“…The main results confirm epidemiologic studies on children's active commuting, which reported positive associations between active commuting and physical activity. [1][2][3]19 These results also confirm positive associations reported from previous walking school bus intervention studies that relied on nonexperimental designs or had small sample sizes but have provided important preliminary data. [15][16][17]19,20 For example, in a quasi-experimental trial, walking school bus children attained ϳ11 more minutes/day of physical activity than control subjects.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The main results confirm epidemiologic studies on children's active commuting, which reported positive associations between active commuting and physical activity. [1][2][3]19 These results also confirm positive associations reported from previous walking school bus intervention studies that relied on nonexperimental designs or had small sample sizes but have provided important preliminary data. [15][16][17]19,20 For example, in a quasi-experimental trial, walking school bus children attained ϳ11 more minutes/day of physical activity than control subjects.…”
Section: Discussionsupporting
confidence: 79%
“…36 Applying the theoretical framework of social cognitive theory at time 1, children's self-efficacy for active commuting was assessed using a 17-item questionnaire (Cronbach's ␣ ϭ 0.75), parents' self-efficacy for allowing their children to actively commute was assessed using a 15-item questionnaire (Cronbach's ␣ ϭ 0.88), and parents' outcome expectations was assessed using a 14-item questionnaire (Cronbach's ␣ ϭ 0.78). 25 …”
Section: Covariatesmentioning
confidence: 99%
See 3 more Smart Citations